ANÁLISE DO CENÁRIO ATUAL DE GESTÃO DOS RESÍDUOS SÓLIDOS DE CONSTRUÇÃO CIVIL (RSCC) NA CIDADE DE ABAETETUBA/PA - Farias Júnior, Claudionor A.; Santana, Wylliam B.; Seixas, Renato de M.; Gomes, Laércio G.; Maues, Luiz M. F. (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
A major source of negative environmental impacts in the the construction industry is constantly seeking to improve its production processes by reducing, reusing or giving appropriate disposal to the waste generated at construction sites. As an alternative to this problem, Resolution 307 of the National Environmental Council (CONAMA) was created. The objective of this work is to evaluate the index of knowledge about this resolution among resident engineers in the city of Abaetetuba / PA and compare them with the capital Belém. Twenty-one works were visited, of which 18 were successful in data collection, and 3 were denied access without specified motivation. As a result, it was noticed that the city has a weak management of its RCC generated and that compared to the state capital, the situation is alarming, with indices of performance well below Belém.